Tree diversity and species identity effects on soil fungi, protists and animals are context dependent - Tedersoo, Leho; Bahram, Mohammad; Cajthaml, Tomáš; Põlme, Sergei; Hiiesalu, Indrek; Anslan, Sten; Harend, Helery; Buegger, Franz; Pritsch, Karin; Koricheva, Julia; Abarenkov, Kessy (The ISME journal, 2016)
Plant species richness and the presence of certain influential species (sampling effect) drive the stability and functionality of ecosystems as well as primary production and biomass of consumers. However, little is known about these floristic effects on richness and community composition of soil biota in forest habitats owing to methodological constraints. We developed a DNA metabarcoding approach to identify the major eukaryote groups directly from soil with roughly species-level resolution. Using this method, we examined the effects of tree diversity and individual tree species on soil microbial biomass and taxonomic richness of soil biota in two experimental study systems in Finland and Estonia and accounted for edaphic variables and spatial autocorrelation. Our analyses revealed that the effects of tree diversity and individual species on soil biota are largely context dependent. Multiple regression and structural equation modelling suggested that biomass, soil pH, nutrients and tree species directly affect richness of different taxonomic groups. The community composition of most soil organisms was strongly correlated due to similar response to environmental predictors rather than causal relationships. On a local scale, soil resources and tree species have stronger effect on diversity of soil biota than tree species richness per se.
Keywords: houby; Soil Microbiology; Finsko; stromy; Eukaryota; biodiverzita; společenstvo; Trees; Fungi; zvířata; Soil; půdní mikrobiologie; Finland; Biodiversity; Biota; Biomass; půda; biomasa; Animals